THE PRACTICES AND APPROACHES OF INTERFAITH DIALOGUE AT LEICESTER, UK - Ramli, Ahmad Faizuddin; Awang, Jaffary (Journal of Techno-Social, 2015)
The diversity of human is one of the God's. With the diversity, people from different religions, ethnics, and cultures can live together and sharing the good values. However, it can only be achieved with dialogue which is perceived as the best mechanism to build mutual understanding and respect with each other. In the context of Leicester, which located in the East Midlands of England, the practices of interfaith dialogue are implemented successfully till today. There are a lot of organizations and people who are involved and organizing interfaith dialogue activities with different approaches. This article will discuss about the practices and approaches of interfaith dialogue in Leicester. The method used in this research was qualitative, which included literature review, observation and participation, and particularly interviews with fifteen people who represented interfaith organization and religious community in Leicester. The findings show the practices of interfaith dialogue have been organized with different types of approaches. In addition, it can be deliberated as a good model of interfaith dialogue particularly for those who want to involve in these activities.